A study of employee perception towards factors influencing the employee motivation: a case study in Majlis Daerah Lahad Datu, Sabah / Michelle Omar Ali and Syahrul Ahmad - Omar Ali, Michelle; Ahmad, Syahrul (Faculty of Administrative Science and Policy Studies, 2012)
This study examines the employee perceptions towards factors that influence the employee motivation in the workplace. In addition, the study also attempts to determine the employee perceptions towards the relationship between factors that influence motivation and the employee perception towards the most factors that influence the employee motivation in the workplace. Questionnaire as been used as a research instruments were used to obtain data. A total of 86 questionnaires for the respondents were mailed to Majlis Daerah Lahad Datu, Sabah. The sample of study and data was then being analyzed using the “Statistical Package for Social Science” (SPSS Window) Version 18.0. The tests involved are Descriptive Analysis, Reliability Analysis, Normality Analysis, Pearson Product Moment Correlation Analysis and Multiple Linear Regression Analysis. The result of found that the employee perception is agreed that the psychological needs, safety needs, social needs, self-esteem needs and self-actualization needs influenced the employee motivation in the workplace. Furthermore, it is also found that the employee perception agreed that the most influential factor in employee motivation is the psychological needs. In addition, some suggestions have been recommended for Majlis Daerah Lahad Datu to increase the employee motivation in the workplace.